Oxygen Enrichment Ameliorates Cardiorespiratory Alterations Induced by Chronic High-Altitude Hypoxia in Rats - Shao, Xi; Dong, Xu; Cai, Jing; Tang, Chi; Xie, Kangning; Yan, Zedong; Luo, Erping; Jing, Da (Frontiers in Physiology, 2021)
Chronic high-altitude hypoxia (HAH) results in compensatory pathological adaptations, especially in the cardiorespiratory system. The oxygen enrichment technology can provide long-lasting oxygen supply and minimize oxygen toxicity, which has proven to be effective to increase oxygen saturation, decrease heart rate, and improve human exercise performance after ascending to high altitudes. Nevertheless, it remains unknown whether oxygen enrichment can resist chronic HAH-induced cardiorespiratory alterations. Thirty-six male rats were equally assigned to the normal control (NC), high-altitude hypoxia (HAH) and high-altitude hypoxia with oxygen enrichment (HAHO) groups. The HAH and HAHO rats were housed in a hypobaric hypoxia chamber equivalent to 5000 m for 4 weeks. The HAHO rats were exposed to oxygen-enriched air for 8 h/day. We found that oxygen enrichment mitigated the augmented skin blood flow and improved the locomotor activity of HAH-exposed rats. Oxygen enrichment inhibited HAH-induced increase in the production of red blood cells. The hemodynamic results showed that oxygen enrichment decreased right ventricular systolic pressure and mean pulmonary artery pressure in HAH-exposed rats. HAH-associated right ventricular hypertrophy and cardiomyocyte enlargement were ameliorated by oxygen enrichment. Oxygen enrichment inhibited HAH-induced excessive expression of cytokines associated with cardiac hypertrophy and myocardial fibrosis (ACE/ACE2, angiotensin II, Col1α1, Col3α1 and hydroxyproline) in the right ventricle. Oxygen enrichment inhibited medial thickening, stenosis and fibrosis of pulmonary arterioles and cytokine expression related with fibrosis (Col1α1, Col3α1 and hydroxyproline) and pulmonary vasoconstriction (endothelin-1) in HAH-exposed rats. This study represents the first effort testing the efficacy of the oxygen enrichment technique on cardiopulmonary structure and function in chronic HAH animals, and we found oxygen enrichment has the capability of ameliorating chronic HAH-induced cardiopulmonary alterations.